2016
DOI: 10.1515/amm-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Input During Disk Laser Bead-On-Plate Welding of Thermomechanically Rolled Steel on Penetration Characteristics and Porosity Formation in the Weld Metal

Abstract: The paper presents a detailed analysis of the influence of heat input during laser bead-on-plate welding of 5.0 mm thick plates of S700MC steel by modern Disk laser on the mechanism of steel penetration, shape and depth of penetration, and also on tendency to weld porosity formation. Based on the investigations performed in a wide range of laser welding parameters the relationship between laser power and welding speed, thus heat input, required for full penetration was determined. Additionally the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
(8 reference statements)
0
22
0
Order By: Relevance
“…The reason for this is the complexity of the absorption of laser radiation, heat generation and heat transfer in the region of welding, especially in a case of a keyhole welding mode. The physical processes mentioned above are influenced by many factors such as power density of the laser beam (laser radiation), temperature of the irradiated surface, time of laser beam irradiation, intensity of metal evaporation, plasma plume formation and many others [34]. It was also found that the plastically deformed metal of the tensile sample broken in the base metal, characterized by maximum tensile strength, is delaminated in the fracture zone, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reason for this is the complexity of the absorption of laser radiation, heat generation and heat transfer in the region of welding, especially in a case of a keyhole welding mode. The physical processes mentioned above are influenced by many factors such as power density of the laser beam (laser radiation), temperature of the irradiated surface, time of laser beam irradiation, intensity of metal evaporation, plasma plume formation and many others [34]. It was also found that the plastically deformed metal of the tensile sample broken in the base metal, characterized by maximum tensile strength, is delaminated in the fracture zone, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 and 6 the microstructure of the weld metal in fusion zone (FZ), as well as the width and microstructure of heat affected zone (HAZ), were significantly dependent on the thermal conditions (heat input) of laser welding and thus subsequent cooling rates. The cooling times between 800 and 500°C were calculated for different heat inputs of autogenous disk laser welding of 5.0 mm thick butt joints of the S700MC steel in the manner described in detail in the ref 34. The results of calculations are given in the Table 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7] This new steel grade shows the strength and yield point (1100 MPa) of quenched and tempered low-alloy steels, while being a low-carbon equivalent at a level similar to the typical thermomechanically rolled, fine-grained, microalloyed steels. [8][9][10][11] To be able to use such high strength and performance of this steel grade in practice, it is necessary to provide at least similar properties of the welded joints.…”
Section: Introductionmentioning
confidence: 87%